Therapeutic help to individuals using and abusing of psychoactive substances - Leandro, Bárbara Rosa Correia; Monteiro, Luiz Henrique Batista; Lucchese, Roselma; Vera, Ivânia; Felipe, Rodrigo Lopes de; Fernandes, Inaina Lara (Rev Rene, 2017)
Objective: to describe the search for the therapeutic help of individuals using and abusing of psychoactive substances. Methods: it is a cross-sectional epidemiology study of individuals from the central-western region of Brazil, with a history of abusive use of psychoactive substances. Face-to-face interviews were conducted at the research sites in a private setting. The data were analyzed by statistical analysis. Results: there were 266 individuals interviewed, 85.3% were male and with an age of onset of use ≥18 years old. Most interviewees reported seeking help in rehabilitation clinics. Prayer was the most frequent intervention, and the professional with the greatest influence was the pharmacist.Conclusion: men were prevalent among those who sought help, and crack was the drug in use reported by most of them.